Measurement, reporting and verification of livestock GHG emissions by developing countries in the UNFCCC: current practices and opportunities for improvement - Wilkes, Andreas; Reisinger, Andy; Wollenberg, Eva Karoline; Dijk, Suzanne van (2017)
This report provides an overview of current practices, challenges and opportunities in the measurement, reporting and verification (MRV) of livestock greenhouse gas (GHG) emissions and emission reductions by developing countries in the context of the United Nations Framework Convention on Climate Change (UNFCCC). MRV of livestock GHG emissions is relevant because (i) livestock production makes a significant contribution to global GHG emissions; (ii) livestock GHG emissions have been contributing an increasing share of agricultural emissions over time; and (iii) better characterization of livestock GHG emissions can assist policy makers to target and design efforts to mitigate GHG emissions. As national climate change mitigation policies increasingly focus on GHG reduction targets in Nationally Determined Contributions (NDCs), this report assesses the extent to which current MRV practices are able to meet the evolving policy needs. The report describes MRV obligations under the UNFCCC (Chapter 2), current practices in compiling and reporting livestock GHG emissions through national GHG inventories (Chapter 3) and MRV of mitigation actions (Chapter 4), and highlights opportunities for improvement (Chapter 5).